Determination of biochemical responses to drought stress in cultivated and exotic wheat genotypes (Journal of the Bangladesh Agricultural University, 2024)
Ten wheat genotypes of locally cultivated and exotic origins were grown under drought condition to determine the biochemical responses. Plants were grown in hydroponics in modified Hoagland solution in box container in the Growth Room with temperature, light and humidity control at the Plant Stress Breeding Laboratory (PSBL), at the dept. of Genetics and Plant Breeding, BAU, Mymensingh. Nutrient solution was refreshed after every ten days. Wheat plants were subjected to drought stress, induced by 3% and 6% polyethylene glycol 6000 (PEG 6000) 6000 in hydroponic solution after 47 days of transferring seedling in full strength nutrient solution. Plants were kept in drought treatment for 42 days and on harvesting, leaves were collected for biochemical assays. Six biochemical traits were determined from leaf tissues following standard protocol. Concentration of leaf biochemical viz. Catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), hydrogen peroxide (H2O2), malondialdehyde (MDH) and proline were found in both increasing and decreasing trend of fluctuation. Not a single genotype was found with the entire biochemical traits with favorable actions, but several genotypes demonstrated relatively better performance compared to control. The relationship among the biochemical traits were also determined and found a positive significant correlation between CAT and POD. A ranking table was also constructed considering mean performance of the genotypes under different PEG 6000 treatment. Considering mean performance, % change of bio-chemicals under drought condition and ranking table, genotypes Sonalika, BARI Gom 21, BARI Gom 29, BARI Gom 30, Summa and Burr were found with better biochemical mechanisms under both 3% and 6% PEG 6000 induced drought and recommend to consider for future wheat improvement program for drought tolerance.J Bangladesh Agril Univ 18(2): 212–220, 2020https://doi.org/10.5455/JBAU.101495